CHARITY IN THE CONTEXT OF MATERIAL LIFE OF NORTH CAUCASIAN ÉMIGRÉS IN FRANCE IN THE 1920-1940s - I. L. BABICH (Кавказология)
The article was prepared on the basis of archival (public and private archives of France) and field ethnographic materials collected by the author in France. The aim of this article is to study one of the aspects of the domestic sphere of life of the North Caucasian émigrés, who settled in France in the 1920s. The author examined various aspects of the material life of emigrants (job, rent flat etc.), various types of emigrant social assistance and its connection with the political views of North Caucasians. Some of North Caucasian émigrés were the rich. They became owners of oil shares (for example, Nobel), the other – very poor people. Many emigrants acquired financial prosperity during the 1930s and 1940s.